Budget oversight in territorial autonomies: A comparative analysis of Hong Kong and Macao. (March 2023) - Fong, Brian C.H.
Traditionally, comparative budgeting scholars have focused on analysing budget oversight at the sovereign state level. Budget oversight at the territorial autonomy level remains largely under-investigated. Drawing on the Open Budget Survey methodology, this study is a pioneering attempt to compare the budget oversight institutions and practices in Hong Kong and Macao under the 'one country, two systems' model. This study finds that the varying practices of budget oversight of Hong Kong and Macao are the consequence of their different bases of opposition politics, including democratic opposition, the media and civil society. This study extends the research focus of existing comparative budgeting literature from sovereign states to territorial autonomies. Thus, it has important implications for budget oversight analysis and policy worldwide. Points for practitioners: This article uses comparative studies of Hong Kong and Macao to illustrate how different bases of opposition politics have led to varying practices of budget oversight. For policymakers, the lesson from the comparative studies is that the rise of democratic opposition, the media and civil society will bring about pressures for budget oversight. More policy learning is necessary for policymakers across democracies and semi-democracies to share the experiences of handling the politics of budget oversight.